Study of Molecular Transport Through Nano-Sized Asymmetric Multipores in the Membrane of a Giant Unilamellar Vesicle Using COMSOL Simulation (Bangladesh Journal of Physics, 2024)
The controlled transport of molecules through cell membrane nanopores holds significant promise for various biomedical applications, ranging from gene transfection and cancer chemotherapy to transdermal drug delivery. Among the diverse array of membrane-active agents, antimicrobial peptides (AMPs) have garnered substantial interest due to their antibacterial and antifungal properties. Magainin 2, initially uncovered within the African clawed frog Xenopus laevis, is one such AMP known to interact with lipid bilayers that lead pore formation induced by membrane-active agents like magainin-2. In this study, we employed simulation techniques using COMSOL Multiphysics to investigate molecular transport of Calcein, Texas-Red Dextran 3000 (TRD-3k), TRD-10k, and AF-SBTI through nanoscale multipores of varying sizes, assessing the impact of both pore diameter and molecular size. Our simulations reveal that the rate constant of molecular transport decreases with increasing fluorescent probe size and pore diameter which comply with experimental observations of inside-to-outside probe leakage.Bangladesh Journal of Physics, Vol. 31, Issue 2, pp. 53 – 65, December 2024